(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Ensuring accuracy of the shape of holes processed by boring is essential for increasing productivity and economy of the process. The great influence for ensuring the prescribed operational and quality indicators during boring is the stability of the technological system and in particular the total deformations. This determines the goal of the present development, namely reduction of elastic deformations and displacements of the elements of the technological system.